2013
DOI: 10.1017/s1368980013000657
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with a low adherence to a Mediterranean diet pattern in healthy Spanish women before pregnancy

Abstract: Objective: To analyse the factors associated with the level of adherence to a Mediterranean dietary pattern in healthy Spanish women before pregnancy. Design: A prospective series of 1175 women. An FFQ validated in Spanish populations served to collect dietary data. The Mediterranean Diet Adherence Index was used to assess the level of adherence to a Mediterranean diet pattern. Polytomic regression was performed to identify the associated factors. Setting: Catchment area of Virgen de las Nieves University Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
32
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 53 publications
(118 reference statements)
7
32
1
Order By: Relevance
“…In the present study, age was the main influential factor in MD adherence, as reported by other researchers [ 34 36 ]. The younger participants tended to follow a less healthy dietary pattern such as the Western diet, as reported in other studies [ 37 39 ].…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, age was the main influential factor in MD adherence, as reported by other researchers [ 34 36 ]. The younger participants tended to follow a less healthy dietary pattern such as the Western diet, as reported in other studies [ 37 39 ].…”
Section: Discussionsupporting
confidence: 86%
“…In the unadjusted and adjusted models, the adherence to a Mediterranean diet increased the probability of quitting smoking during pregnancy. This is in line with previous research showing that smoking and a lack of exercise were associated with a lower adherence to a Mediterranean diet before pregnancy, and that in the adult population, being a current smoker was associated with a lower adherence to a Mediterranean diet …”
Section: Discussionmentioning
confidence: 99%
“…Benefits of high adherence to MD and of adequate folate intake are reported in the general population (Sofi et al 2010 ; Couto et al 2011 ; Tamura and Picciano 2006 ), and particularly in women of childbearing age, because of the effect of diet on their health and well-being, on pregnancy outcome, and on newborns’ health (Tamura and Picciano 2006 ; Barchitta et al 2014b ; Olmedo-Requena et al 2013 ). Besides, recent studies provide evidence for a beneficial role of the MD on endometrial (Filomeno et al 2015 ) and breast cancer risk (Buckland et al 2013 ; Castellò et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%